P89 Transarterial chemoembolization as neo-adjuvant therapy pre-transplantation in patients with hepatocellular carcinoma. (16th November 2010) - Tsochatzis, E; Garcovich, M; Marelli, L; Fede, G; Germani, G; O'Beirne, J; Burroughs, A
Abstract : Introduction: Hepatocellular carcinoma (HCC) is the main indication for 15% of liver transplants. Currently the criteria used for listing patients are the Milan criteria. However, as waiting time is increasing, patients may fall out these criteria while on the waiting list. Aim: We retrospectively evaluated the effect of neo-adjuvant transarterial chemoembolization (TACE) in consecutive patients transplanted for HCC. Method: We analysed data from consecutive patients who were transplanted for HCC between 1990 and 2010 as main indication in our unit. Laboratory, epidemiological, radiological and histological data were analysed. Survival was evaluated using multiple regression analysis. Results: In total 148 patients were transplanted for HCC, of which 74 had TACE as neo-adjuvant therapy. Mean follow-up post-transplant was 31±29 months (range 1–145). Patients had a mean of 1.6±0.9 (range 1–5) TACE sessions and had a mean waiting list time of 2.5±2.4 months (range 0.5–12.3). TACE response was evaluated in explanted livers as follow: no response in 10 (16%), partial tumour necrosis in 35 (55%) and complete tumour necrosis in 19 (30%). Tumour recurred in 21 (14%) patients in a mean time of 5.1±14 months. Recurrence happened in 2/10 patients who did not respond to TACE, 1/35 who had a partial response and 0/19 who had a complete response (p=0.040). TACE as neo-adjuvant therapy was associated with less recurrence irrespective of histological response (18.3% recurrence in patients who did not have TACE vs 5.6% in patients who had, p=0.037). No serious adverse effects of TACE were noted. Conclusion: TACE is an effective neo-adjuvant therapy in patients listed for liver transplantation, as it is associated with significantly less post-transplantation tumour recurrences. As waiting lists are getting longer, its use as a standard neo-adjuvant therapy should be further explored.